Correlation between Woody Species and Environmental Variables in a Tropical Forest in Central Laos - Van Cuong, Le; Van Hop, Nguyen; Khamphet Phomphoumy; Chi Thinh, Pham; Thanh Trang, Pham (Journal of Forestry Science and Technology, 2024)
The tropical forest biome serves as a significant focal point for conservation endeavors. However, understanding the variations in woody plant composition and the underlying driving factors remains limited. The vegetation gradient within Phou Khao Khouay (PKK) National Park in central Laos presents an intriguing environmental model for investigating these patterns. This study, conducted within PKK National Park, aims to classify woody plant communities of three different forest types: mixed deciduous forest (MDF), dry evergreen forest (DEF), and mixed coniferous forest (MCF), utilizing both the phytosociology approach and multivariate analysis. Data from 32 permanent plots (each measuring 50 m × 50 m) were analyzed, revealing 5,477 tree individuals with a diameter at breast height (DBH) ≥ 5 cm, representing 194 woody species from 64 families and 133 genera. The results indicate significant diversity at the family and genus levels, identifying four distinct plant communities and 44 indicator species based on Tichy and Chytry’s phi coefficient method. Stability characterizes the MCF forest type, while the stands of DEF and MDF exhibit differentiation into three communities each. Notably, high heterogeneity in species composition and environmental conditions is evident, with elevation and soil nutrient levels (specifically total phosphorus and total potassium) emerging as primary influencers on species coexistence. The study also highlights correlations between woody plant species composition and topographic and soil variables. These findings underscore the importance of identifying microhabitats conducive to growing and conserving woody plant species within PKK National Park for future research and conservation efforts.